1997
DOI: 10.1002/art.1780400308
|View full text |Cite
|
Sign up to set email alerts
|

Breast implants in patients with differentiated and undifferentiated connective tissue disease

Abstract: Objective. To assess the frequency of breast implantation and the relationship of the implants to the onset of symptoms in patients with differentiated and undifferentiated connective tissue disease (CTD).Methods. We evaluated an inception cohort of patients with differentiated and undifferentiated CTD and symptoms of <12 months duration when enrolled in 1983-1987. The risk of having breast implants in those patients with early symptoms of CTD was determined in comparison with that in a non-concurrent control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 22 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…Undifferentiated CTD was accepted by the authors as the term for atypical CTD because it has a clear case definition, is distinct from the other established CTDs, and has substantive symptoms. 61 Lipworth et al 41 performed an updated review of the results of epidemiologic studies published since 1999 2,55,62-66 and concluded that the results of several studies provide no evidence of a higher frequency of undefined CTD among women with cosmetic breast implants or of a rheumatic symptom profile unique to these women and/or indicative of a specific atypical CTD.…”
Section: Breast Cancer Detectionmentioning
confidence: 97%
“…Undifferentiated CTD was accepted by the authors as the term for atypical CTD because it has a clear case definition, is distinct from the other established CTDs, and has substantive symptoms. 61 Lipworth et al 41 performed an updated review of the results of epidemiologic studies published since 1999 2,55,62-66 and concluded that the results of several studies provide no evidence of a higher frequency of undefined CTD among women with cosmetic breast implants or of a rheumatic symptom profile unique to these women and/or indicative of a specific atypical CTD.…”
Section: Breast Cancer Detectionmentioning
confidence: 97%
“…between silicone breast implants and CTD have been published. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] All [22][23][24][25][26][27][28][29][30][31][32][33][35][36][37][38][39][40] but one 34 have failed to demonstrate an increased risk of systemic sclerosis or any other CTDs. The one study 34 that found a small, but significant, excess of CTD was based on self-reporting of diseases, the subsequent validation of reported CTDs found evidence for overreporting, as only 22.7% of the self-reported cases could be confirmed.…”
Section: Original Investigationmentioning
confidence: 99%
“…Although many aspects of the local immune response to silicone have been elucidated, it is still unclear whether women with silicone breast implants experience a systemic activation of their immune systems. Several studies showed increased prevalence of serologic markers of connective tissue diseases such as rheumatoid arthritis, systemic lupus erythematosus, mixed connective tissue disease, polymyositis or scleroderma [9][10][11], but even metaanalyses have not provided an unequivocal link between SMI and systemic autoimmune diseases [12,13]. In contrast to these metaanalyses, there are numerous case reports of SMI patients showing defined rheumatologic disorders that were greatly ameliorated by implant removal [14].…”
Section: Introductionmentioning
confidence: 98%